Pengaruh Kekayaan Daerah, Dana Perimbangan, dan Belanja Daerah Terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten/Kota di Provinsi Sumatera Selatan - Bambang Cahyadi; Sukmini Hartati; Sri Hartaty (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of Regional Wealth, Revenue Sharing Funds (Dana Perimbangan), and Regional Expenditures on the Financial Performance of Local Governments in Regencies/Cities within South Sumatra Province. This research adopts a quantitative approach using secondary data obtained from the budget realization reports (APBD) of 17 regencies/cities during the period from 2020 to 2023. The population in this study includes all local governments in South Sumatra Province, and the sampling technique used is a saturated sample, in which all members of the population are used as the research sample. The analytical method employed is multiple linear regression with the assistance of SPSS software. The results of the study indicate that Regional Wealth has a positive and significant effect on Local Government Financial Performance, while Revenue Sharing Funds have a negative and significant effect. Meanwhile, Regional Expenditures do not have a significant influence on Financial Performance. Simultaneously, all three independent variables significantly influence the Financial Performance of Local Governments. These findings suggest that optimizing Local Own-Source Revenue and managing transfer funds and regional expenditures efficiently are key factors in improving fiscal performance at the regional level.